Association of monocyte tumor necrosis factor α expression and serum inflammatory biomarkers with walking impairment in peripheral artery disease - Pande, Reena L.; Brown, Jonathan; Buck, Stewart; Redline, Whitney; Doyle, Jeanne; Plutzky, Jorge; Creager, Mark A. (Journal of vascular surgery, 2015)
Inflammation contributes to the development of peripheral artery disease (PAD) and may contribute to intermittent claudication by adversely affecting vascular and skeletal muscle function. We explored the association of inflammation to maximal walking time (MWT) in patients with claudication. Circulating inflammatory biomarkers, including tumor necrosis factor α (TNF-α), C-reactive protein (CRP), interleukin-6 (IL-6), and soluble intercellular adhesion molecule 1 (sICAM), were measured in 75 subjects with intermittent claudication as well as in 43 healthy subjects. Real-time polymerase chain reaction was used to quantify mRNA expression of TNF-α, IL-6, interferon-γ, and CD36 from peripheral blood monocytes. Treadmill testing was performed in PAD subjects to assess MWT. Compared with healthy subjects, PAD subjects had higher levels of circulating TNF-α (P < .0001), CRP (P = .003), sICAM (P < .0001), and IL-6 (P < .0001). Expression of both IL-6 (P = .024) and CD36 (P = .018) was greater in PAD subjects than in healthy subjects. Among subjects with PAD, higher gene expression of TNF-α was associated inversely with MWT (P = .01). MWT was also associated inversely with greater levels of circulating TNF-α (P = .028), CRP (P = .024), IL-6 (P = .03), and sICAM (P = .018). Systemic inflammation, as indicated by TNF-α inflammatory gene expression in peripheral blood monocytes and by circulating biomarker levels, is associated with impairment in walking time in patients with PAD and intermittent claudication.